2009
DOI: 10.1038/nmeth.1399
|View full text |Cite
|
Sign up to set email alerts
|

A genetically encoded reporter of synaptic activity in vivo

Abstract: To image synaptic activity within neural circuits, we have tethered the genetically-encoded calcium indicator (GECI) GCaMP2 to synaptic vesicles by fusion to synaptophysin. The resulting reporter, SyGCaMP2, detects the electrical activity of neurons with two advantages over existing cytoplasmic GECIs: the locations of synapses are identified and the reporter displays a linear response over a wider range of spike frequencies. Simulations and experimental measurements indicate that linearity arises because SyGCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
217
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(223 citation statements)
references
References 33 publications
(50 reference statements)
5
217
1
Order By: Relevance
“…However, until now it has not been widely used probably because it is not easy to analyze the calcium transient with a poor signal-to-noise ratio. GCaMP1.6 and GCaMP2 were successfully used to detect calcium signals in the neuropil of the zebrafish tectum, which consisted of axonal arbors of retinal ganglion cells and dendritic arbors of the tectal cells (26,27). In contrast to these studies, our present study clearly demonstrated that GCaMP-HS can detect calcium signals in both the cell bodies and neurites.…”
Section: Alternating and Synchronized Periodic Activation Of The Motorcontrasting
confidence: 66%
“…However, until now it has not been widely used probably because it is not easy to analyze the calcium transient with a poor signal-to-noise ratio. GCaMP1.6 and GCaMP2 were successfully used to detect calcium signals in the neuropil of the zebrafish tectum, which consisted of axonal arbors of retinal ganglion cells and dendritic arbors of the tectal cells (26,27). In contrast to these studies, our present study clearly demonstrated that GCaMP-HS can detect calcium signals in both the cell bodies and neurites.…”
Section: Alternating and Synchronized Periodic Activation Of The Motorcontrasting
confidence: 66%
“…Here, by imaging presynaptic Ca 2+ 17 and mitochondrial positioning in multiple terminals of the same axon, we show that mitochondrial occupancy determines presynaptic Ca 2+ responses and can also affect vesicular release. Moreover, we demonstrate that mitochondrial localisation at presynaptic terminals is tuned by long‐term changes in network activity dependent on Miro1‐mediated mitochondrial trafficking.…”
Section: Introductionmentioning
confidence: 85%
“…Because of the prominent role of calmodulin in a variety of Ca 2þ -dependent pathways, including long-term potentiation (39), extending previously obtained results to cooperative buffering is important. Better tools for describing cooperative buffering may also help in interpreting imaging data obtained with the latest genetically encoded calmodulin-derived Ca 2þ indicator dyes (40)(41)(42)(43). More accurate description of binding dynamics of these dyes may help in increasing the temporal resolution of Ca 2þ imaging obtained using these synthetic buffers.…”
Section: Discussionmentioning
confidence: 99%